Language Politeness as a Foundation for Ethical and Moral Development Among Islamic Elementary School Students - Ridwan, M; Hodairiyah, Hodairiyah; Sulistiyono, Sulistiyono (STAI Hubbulwathan Duri, 2024)
The principles of politeness are fundamental to understanding ethical and moral behavior. This study explores the principles of politeness, as manifested in maxims, and the ethics and morals of students at Islamic Elementary School. The method used in providing data is the Listen method with Dasar Sadap techniques with Simak, Bebas, Libat Cakap (SBLC) technique. Data was obtained from 25 students' oral and written speech. The oral speech data was collected by dialogue using a recorder and transcript. Then, written speech data was taken from the transcript of the message. The research uses a pragmatic theoretical approach, especially the principles of language politeness (Leech, 1983). The data analyzed uses the collection method with Bagi Unsur Langsung (BUL) technique. This technique divided data directly into the theory, although the results of the research show that the language use of Nurul Islam students does not violate the principles of politeness. In that sense, students' speech is classified as using polite language, which is manifested in the form of (1) the maxim of wisdom (tact maxim), (2) maxim of generosity or generosity (generosity maxim), (3) maxim of acceptance or praise or appreciation (approbation maxim), (4) humility or simplicity maxim (5) agreement maxim, (6) sympathy maxim. These maxims shape student ethics and morals in the midst of rapidly increasing technological developments through the language conveyed in the interactions carried out. Thus, this research contains the politeness principle Islamic Elementary School Studets used. Social media do not influence the language used of politeness principle, although the research still has the potential to be studied in more depth regarding the principles of politeness from different perspectives and objects in rapid technological advancements.